2018
DOI: 10.3390/nu10040495
|View full text |Cite
|
Sign up to set email alerts
|

Blackcurrant Anthocyanins Increase the Levels of Collagen, Elastin, and Hyaluronic Acid in Human Skin Fibroblasts and Ovariectomized Rats

Abstract: Blackcurrants (Ribes nigrum L.) contain high levels of anthocyanin polyphenols, which have beneficial effects on health, owing to their antioxidant and anticarcinogenic properties. Phytoestrogens are plant-derived substances with estrogenic activity, which could have beneficial effects on the skin. Estradiol secretion decreases during menopause, reducing extracellular matrix (ECM) component production by skin fibroblasts. Using a normal human female skin fibroblast cell line (TIG113) and ovariectomized rats, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
46
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 49 publications
7
46
0
2
Order By: Relevance
“…Consistently, a mixture of plant oils including A. rugosa alleviated the atopic dermatitis-induced skin barrier damage [19]. In addition, as a natural moisturizing factor, HA, which is one of the abundant molecules in the dermis, plays an important role in retaining moisture levels [20]. Thus, the level of HA, which depends on three different HAS isoforms is a representative element of skin moisture [13].…”
Section: Discussionmentioning
confidence: 95%
“…Consistently, a mixture of plant oils including A. rugosa alleviated the atopic dermatitis-induced skin barrier damage [19]. In addition, as a natural moisturizing factor, HA, which is one of the abundant molecules in the dermis, plays an important role in retaining moisture levels [20]. Thus, the level of HA, which depends on three different HAS isoforms is a representative element of skin moisture [13].…”
Section: Discussionmentioning
confidence: 95%
“…MMP expression induced by UVB exposure contributes to the skin wrinkle formation by promoting the degradation of ECM, including collagen fibers [26]. An anthocyanin-rich extract has phytoestrogenic activities and is known to upregulate the expression of collagen and elastin [10]. In addition, various studies to address the above problems have shown that dietary supplements containing vitamins, antioxidants, collagen peptides, and pre-and probiotics have positive effects on skin elasticity [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…These results are promising in that they suggest BC and BCE have the potential to be used as therapies for the treatment of ophthalmological diseases. It was reported by Nanashima et al (2018) that treatments with BCE increased collagen, elastin, and hyaluronic acid in human skin fibroblasts and ovariectomized rats. This study used normal human female skin fibroblast cells (TIG113), OVX female Sprague-Dawley rats (12 weeks old) that had their ovaries removed to simulate menopausal women, and sham surgery rats (Nanashima et al, 2018).…”
Section: Concise Reviews and Hypotheses In Food Sciencementioning
confidence: 97%
“…Results from this study indicated that TIG113 cells that were exposed to BCE had similar effects to TIG113 cells that have been exposed to estradiol. The results from the OVX rat study indicated that the thickness of the collagen was significantly greater in those treated with 3% BCE (1,156 ± 36 µm) and in sham rats (845 ± 36 µm) (Nanashima et al., ). Therefore, it was made evident that BCE, particularly the four major compounds (D3G, D3R, C3G, and C3R) in BCE, produce phytoestrogen effects, which are favorable for the skin (Table ).…”
Section: Health Benefits Of Bioactive Compounds From Bcmentioning
confidence: 99%
See 1 more Smart Citation